Comminution of carbon particles in a fluidized bed reactor: A review. (April 2023) - Manzoor, Sama; Tatum, James; Wani, Omar B.; Bobicki, Erin R.
Highlights: Comminution impact on fluidized bed combustion of carbon fuels have been reviewed. Factors that affect comminution in fluidized bed reactor have been discussed. Fines generation and their afterburning increase coarse char combustion rate. Carbon loss via elutriation is crucial in low reactive fuels. Initial particle size and distribution change depending on fuel type. Abstract: Study of comminution of carbonaceous solids during fluidized bed combustion process is essential for understanding the actual combustion rate, thermal efficiency, and particle size distribution. Comminution in a fluidized bed reactor involves a sequence of events that occur either separately or simultaneously, and with combustion process. These events are: primary fragmentation, which is attributed to stresses caused by devolatilization; secondary fragmentation, which is due to the burning up of the linkages inside the char particles; percolative fragmentation, which is a result of internal burning; and attrition, which occurs by collisions with other particles, or with the surface of the reactor. Several studies have demonstrated that due to the impact of particle comminution within the fluidized bed reactor, the carbon conversion efficiency is significantly affected. Furthermore, fine particles produced by comminution are elutriable, and they reduce the fuel residence time as well as thermal efficiency due to incomplete carbon conversion. Hence, there is a need for a complete understanding of particle comminution during practical combustion process in order to increase conversion efficiency. Considering the last review about this topic was written in 1991, the objective of this paper is to provide an updated overview of recent studies on comminution of carbon-based fuels in a fluidized bed reactor. The paper discusses different types of comminutions and their impacts on reactor efficiency, summarizes the experimental set ups used to investigate particle fragmentations, and presents the discussion on different factors of feed fuels that affect particle fragmentation. Literature experiments revealed that primary and secondary fragmentation greatly influence the fuel particle size and distribution, thus ignoring comminution phenomena will lead to errors while assessing actual fuel particle size in the reactor. It was found that fines generation and their postcombustion can cause increase in coarse char combustion rate. Carbon loss by elutriation is substantial in case of low reactive fuels only. Factors such as porosity, particle size, volatile content, and bed temperature heavily influence particle fragmentation. Fragmentation is also influenced by the initial particle size which in turn effects the particle size after de-volatilization and the size distribution throughout the reactor bed. The average size of the particles after de-volatilization and predictions of the size distributions were found to change depending on fuel type.